2019
DOI: 10.1111/beer.12247
|View full text |Cite
|
Sign up to set email alerts
|

Dare to be different? Investigating the relationship between analyst categorisation hierarchies and corporate social responsibility (CSR) conformity

Abstract: This paper investigates how analyst categorisation hierarchies (CH) affect corporate social responsibility (CSR) conformity. We argue that firms that are labelled as either high rank or low rank by analysts have higher institutional immunity, while firms that are categorised as middle rank have lower immunity. These heterogeneous institutional immunities will affect the levels of CSR conformity differently. Our results, which originate from a sample of Chinese listed firms from 2009 to 2016, suggest that CH ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(32 citation statements)
references
References 64 publications
1
31
0
Order By: Relevance
“…In this case, the global corporate social responsibility of the company acts as a reference which exerts a direct influence on the choice of entry mode, compared to the moderating role of local social responsibility of the host country. This agrees with the findings of Pan et al (2020) that suggests that the effectiveness of CSR practices in terms of differentiation largely varies with the extent to which audiences appreciate the firm's differentiation efforts.…”
Section: Managerial Implicationssupporting
confidence: 90%
“…In this case, the global corporate social responsibility of the company acts as a reference which exerts a direct influence on the choice of entry mode, compared to the moderating role of local social responsibility of the host country. This agrees with the findings of Pan et al (2020) that suggests that the effectiveness of CSR practices in terms of differentiation largely varies with the extent to which audiences appreciate the firm's differentiation efforts.…”
Section: Managerial Implicationssupporting
confidence: 90%
“…Following this differentiation logic, focal firms’ CSR should be different from peers’ CSR. However, some scholars also suggested that CSR is just a symbolic tool to show firms’ conformity to external institution environments (Pan et al , 2020; Zhang et al , 2020). Following this conformity logic, focal firms’ CSR should increase with the increase of peers’ CSR.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…For a particular firm, its peers’ CSR is measured by the average CSR of all firms within the same industry except the firm considered (Gao and Hafsi, 2015). Prior studies usually use industry average as a reference point when computing CSR conformity or differentiation (Pan et al , 2020; Zhang et al , 2020). Thus, we believe this operationalization is proper to identify the peers.…”
Section: Methodsmentioning
confidence: 99%
“…Institutional theory has long been recognised as an effective way to explain how firms participate in environmental innovation. According to institutional theory, firms should comply with the prevailing institutional demands that firms mostly rely on, and non‐conformity will lead to firms being deemed illegitimate and outsiders in the market (Pan, Chen, Yang, & Chen, 2020). DiMaggio and Powell (1983) suggested that firms’ strategies are shaped by institutional pressures from where they are located.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…How will firms respond when they are facing two conflicting institutional forces simultaneously? Firms often establish certain organisational structures, production processes and organisational cultures to satisfy the demands of institutional logics and accrue benefits such as credibility and legitimacy from their fulfilment (Pan, Chen, Yang, et al, 2020). The more one stakeholder matters, the more likely it is that firms will gear their systems towards the stakeholder's expectations.…”
Section: Theory and Hypothesesmentioning
confidence: 99%